A Modal Pushover Analysis on Multi-Span Concrete Bridges to Estimate Inelastic Seismic Responses - Ima Muljati; Pennung Warnitchai (Institute of Research and Community Outreach - Petra Christian University, 2007)
The performance of Modal Pushover Analysis (MPA) in predicting the inelastic seismic response of multi-span concrete bridges is investigated. The bridge is subjected to lateral forces distributed proportionally over the span of the bridge in accordance to the product of mass and displaced shape. The bridge is pushed up to the target displacement determined from the peak displacement of the nth mode inelastic Single Degree of Freedom System derived from Uncoupled Modal Response History Analysis (UMRHA). The peak response from each mode is combined using Square-Root of Sum-of-Square (SRSS) rule. Although the use of SRSS rule is not appropriate in this bridge and the displaced pattern is shifted from the elastic shape due to yielding, MPA can predict well the total peak response of the bridge in inelastic range.